A Comparative study of Warm needling and Bee Venom Pharmacopuncture on Osteoarthritis of the Knee - a Randomized Controlled Trial - - Ka Ram Yang; Ho Sueb Song (Korean Pharmacopuncture Institute, 2008)
Objective : This study was performed to investigate whether Bee Venom Pharmacopuncture(BVP) could be a more effective modality than Warm Needling(WN) in relieving pain and symptoms of knee osteoarthritis(OA). Design : Prospective, randomized and controlled clinical trial. Setting : Single center trial in Korea Patients : 49 volunteers with knee OA participated in the study. All the participants were screened through an inclusion and exclusion criteria. 33 participants were completed the clinical trial. Intervention : The subjects were randomly assigned to one of two groups. One group received BVP(n=18), while the other group received WN(n=15). Sixteen sessions of BVP or WN were given at the pain region of the problematic knee for 8 weeks. Outcome measures : Primary outcome measure is the Korean translation of Western Ontario and McMaster Universities Osteoarthritis Index scores(Korean WOMAC, KWOMAC). Secondary outcome measure is the physical health scores based on the 36-Item Short-Form Health Survey(SF-36) and Patient Global Assessment(PGA). KWOMAC and SF-36 were measured third (baseline, 4 and 8 weeks). PGA was measured twice(4 and 8 weeks). Results : BVP group showed significant decrease compared to WN group in pain, function and total scores of KWOMAC according to the Mann-Whitney U-test. In the PGA, BVP group, compared to WN group, showed a significant increase. Conclusions : BVP was more effective in relieving pain of knee OA than WN. These findings suggest that BVP is a promising alternative for treating knee OA.